Electronic Cigarette Use Intentions Mediate the Association between Low Self-Control and Future Use by Internalizing Symptoms. (15th October 2022) - Sutherland, Benjelene D.; Sutherland, Matthew T.; Trucco, Elisa M.
Abstract: Background : Adolescent electronic (e-)cigarette use intentions are related to initiation. Low self-control is also a risk factor for early stages of substance use. Yet, the impact of low self-control on use through intentions may vary across individuals; depression and anxiety may affect this association. Methods : A sample of 200 adolescents who completed waves 1 and 2 of an ongoing longitudinal study were assessed. We hypothesized that high internalizing symptoms would moderate the indirect effect of low self-control on actual e-cigarette use through e-cigarette use intentions. Results : The mediation pathway was significant at high levels of internalizing symptoms, but not at low or moderate levels. Conclusion : Specifically, those with low self-control and high internalizing symptomatology endorsed the highest e-cigarette use intentions and were more likely to subsequently use e-cigarettes. Youth low in self-control and high in depression and anxiety might be at increased risk to initiate e-cigarette use compared to youth high in self-control and high in internalizing symptomatology.